ANALISIS IKON DAN INDEKS DALAM SEMIOTIKA CHARLES SANDERS PIERCE PADA FILM DOKUMENTER “KAWALI, IDENTITAS LAKI-LAKI BUGIS” - Saifullah, Saifullah; Asrullah, Asrullah; Asrifan, Andi; Zain, Suardi; Yusmah, Yusmah; Rasyid, Rustam (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe Icons and Indexes in Charles Sanders Peirce's semiotics in the documentary film “Kawal, Bugis Male Identity”. This study uses the theory of Charles Sanders Peirce which is often referred to as the "Grand Theory" in semiotics. Grand theory consists of three elements, namely sign, object, and interpretant. The method used in this study is a qualitative descriptive method. The data in this study are in the form of a documentary film "Kwali, Bugis Male Identity" which was uploaded on Youtube "Colle Malli" on April 5, 2016. The source of this research data is written documents regarding kawali and making kawali both thesis and articles on the internet. The data collection technique used is literature study. The data analysis technique used is according to the Miles and Hubermen model, namely:data reduction, data presentation, conclusion drawing. Based on the research results from the documentary film "Kwali, Bugis Male Identity" on aspects of semiotics which include icons and indexes using Charles Sanders Peirce theory, it can be concluded as follows: from the results of the research, the data obtained reached 29 data consisting of 4 data icons with a percentage 13.80% and an index of 25 data with a percentage of 83.20%.